Hakluytus Posthumus or Purchas His Pilgrims in Twenty Volumes Volume II - Purchas, S. (James Maclehose and Sons, 1905)
Containing a description of all the Circumnavigations of the Globe; and the Navigations and Voyages of Englishmen, along the Coasts of Africa, to the Cape of Good Hope, and from thence to the Red Sea, the Abassine, Arabian, Persian, Indian Shores, Continents and islands
Collection
Keywords: Pilgrims; Voyages; Hakluytus Posthumus; Abassine